2001
DOI: 10.1161/01.cir.103.6.871
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Characterization of the Peri-Infarction Zone of Reperfused Myocardial Infarction With Necrosis-Specific and Extracellular Nonspecific Contrast Media

Abstract: Background-Because ischemically injured myocardium is frequently composed of viable and nonviable portions, a method to discriminate the two is useful for clinical management. Methods and Results-Ischemically injured myocardium was characterized with extracellular nonspecific (Gd-DTPA) and necrosis-specific (mesoporphyrin) MR contrast media in rats. Relaxation rates (R1) were measured on day 1 and day 2 by inversion-recovery echoplanar imaging. Spin-echo imaging was used to define contrast-enhanced regions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(167 citation statements)
references
References 40 publications
5
155
0
7
Order By: Relevance
“…4 As a result, it has been postulated that hyperenhanced myocardium detected clinically could also include significant amounts of damaged noninfarcted tissue and, thus, would reflect viable rather than nonviable myocardium. 6,13,14 In support of this, Dendale et al 15 reported inotropic response in 41% of hyperenhanced segments, suggesting viability. Rogers et al 6 also reported that regions presenting delayed hyperenhancement alone or in combination with early hypoenhancement improved circumferential shortening between 1 and 7 weeks after acute MI and would, therefore, be viable.…”
Section: Ce Mri For Prediction Of Segmental Functional Recoverymentioning
confidence: 75%
“…4 As a result, it has been postulated that hyperenhanced myocardium detected clinically could also include significant amounts of damaged noninfarcted tissue and, thus, would reflect viable rather than nonviable myocardium. 6,13,14 In support of this, Dendale et al 15 reported inotropic response in 41% of hyperenhanced segments, suggesting viability. Rogers et al 6 also reported that regions presenting delayed hyperenhancement alone or in combination with early hypoenhancement improved circumferential shortening between 1 and 7 weeks after acute MI and would, therefore, be viable.…”
Section: Ce Mri For Prediction Of Segmental Functional Recoverymentioning
confidence: 75%
“…Namely, low-intensity LGE, approximately 2-3 S.D. above remote myocardium, corresponds to a border zone around infarcts comprised of viable myocytes interspersed within fibrosis [24][25][26], where as more the intermediate/high-intensity LGE corresponds to completely necrotic or fibrotic tissue. Given the entirely different pathophysiology of HCM, the significance of different intensities of LGE cannot be inferred from the MI literature.…”
Section: Discussionmentioning
confidence: 99%
“…35 With the combination of the inversion recovery technique described by Simonetti et al, 36 it became possible to maximize the contrast between viable and 37,38 There is significant decrease in the total extent of LGE between day 1 and day 7 post-MI. [39][40][41] CMR can be used in assessing MI size up to 1 week after the acute ischemic event. With time, the size of the infarct decreases as a result of resolution of tissue edema and gradual contraction of the resultant scar tissue by as much as 25% over a period of 4-8 weeks.…”
Section: Late Gadolinium Enhancementmentioning
confidence: 99%